Semi-automated Database Design by the End-user - d’Hollosy, W.; Walrave, M. H. F.; Hendriks, B. Th.; Debruyne, F. M. J.; Wijkstra, H. (Methods of Information in Medicine, 1995)
An information system was developed to manage the data for a large number of research projects simultaneously. The system, called URIS, has facilitated the management of research data in an academic urological department. It enables end-users, who are not necessarily skilled computer scientists, to design their own databases semi-automatically, by supporting data entry screen design and the specification of research items. The system creates the database tables automatically after these activities. The specification of research items is the most important but also most difficult part in this process.
Keywords: Information Systems; Databases; Data Management; Semi-automated Database Design